GlpD and PlsB Participate in Persister Cell Formation in Escherichia coli - Spoering, Amy L. (American Society for Microbiology, 2006)
Bacterial populations produce dormant persister cells that are resistant to killing by all antibiotics currently in use, a phenomenon known as multidrug tolerance (MDT). Persisters are phenotypic variants of the wild type and are largely responsible for MDT of biofilms and stationary populations. We recently showed that a hipBA toxin/antitoxin locus is part of the MDT mechanism in Escherichia coli. In an effort to find additional MDT genes, an E. coli expression library was selected for increased survival to ampicillin. A clone with increased persister production was isolated and was found to overexpress the gene for the conserved aerobic sn-glycerol-3-phosphate dehydrogenase GlpD. The GlpD overexpression strain showed increased tolerance to ampicillin and ofloxacin, while a strain with glpD deleted had a decreased level of persisters in the stationary state. This suggests that GlpD is a component of the MDT mechanism. Further genetic studies of mutants affected in pathways involved in sn-glycerol-3-phosphate metabolism have led to the identification of two additional multidrug tolerance loci, glpABC, the anaerobic sn-glycerol-3-phosphate dehydrogenase, and plsB, an sn-glycerol-3-phosphate acyltransferase.